Potentiometric Multisensory Systems with Novel Ion-Exchange Polymer-Based Sensors for Analysis of Drugs - Olga V. Bobreshova; Anna V. Parshina; Ksenia A. Polumestnaya (International Journal of Electrochemistry)
This paper examines potentiometric multisensory systems that consist of novel cross-sensitive PD-sensors (Potential Donnan-sensors). The analytical signal of PD-sensors is the Donnan potential at the ion-exchange polymer/electrolyte test solution interface. The use of novel sensors for the quantitative analysis of multicomponent aqueous solutions of amino acids, vitamins and medical substances is based on protolytic and ion-exchange reactions at the interfaces of ion-exchangers and test solutions. The potentiometric sensor arrays consist of PD-sensors and ion-selective electrodes. Such systems were developed for the multicomponent quantitative analysis of lysine monohydrochloride, thiamine chloride and novocaine hydrochloride solutions that contained salts of alkaline and alkaline-earth metals, as well as for mixed solutions of nicotinic acid and pyridoxine hydrochloride. Multivariate methods of analysis were used for sensor calibration and the analysis of the total response of sensor arrays. The errors of measurement of the electrolytes in aqueous solutions did not exceed 10%. The developed multisensory systems were used to determine the composition of a therapeutic “Mineral salt with low content of sodium chloride” and to determine concentrations of novocaine in sewage samples from a dental clinic.